Playing Mahjong for 12 Weeks Improved Executive Function in Elderly People With Mild Cognitive Impairment: A Study of Implications for TBI-Induced Cognitive Deficits - Zhang, Han; Peng, Yi; Li, Chunliu; Lan, Hong; Xing, Guoqiang; Chen, Zhu; Zhang, Bo (Frontiers in Neurology, 2020)
Background : Mild cognitive impairment (MCI) is common among old people. So far effective treatment is lacking that can stabilize or reverse cognitive decline associated with MCI. Recent studies suggest that playing mahjong may improve the attention and memory in the elderly. But its effect on the executive function remains unknown. Methods : Fifty-six old people (74.3±4.3 years of age) with MCI from the first Nursing Home of Nanchong city were randomized into mahjong and control groups (N=28, each group). Subjects in the mahjong group played mahjong 3 times a week for 12 weeks while people in the control group only assumed normal daily activity. The executive function was evaluated using the Montreal Cognitive Assessment–Beijing edition (MoCA-B), the Shape Trail Test (STT) and The Functional Activities Questionnaire (FAQ) before, and at 6 and 12 weeks after the mahjong administration. Results : There were no baseline differences in MoCA-B, STT and FAQ between the two groups. The scores of MoCA-B, STT, and FAQ, however, improved significantly in the mahjong group but not in the control group after the 12-week mahjong administration. Significant correlations were also found between STT and FAQ scores. Conclusions: Playing Mahjong for 12 weeks improved the executive function of the elderly with MCI. Because Mahjong is a simple low-cost entertainment activity, it could be applied to slow down or reverse the progression of cognitive decline in people with MCI including those with traumatic brain injury.